2020
DOI: 10.3389/fmars.2020.594378
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment Disruption and the Role of Unaffected Populations for Potential Recovery After the Pinna nobilis Mass Mortality Event

Abstract: Post-MME Recruitment Pinna nobilis were recorded in a few sites where the resident population had been decimated. This hints to the importance of unaffected populations as larval exporting sources and the role of oceanographic currents in larval transport in the area, representing a beacon of hope in the current extremely worrying scenario for this emblematic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…However, as expected, we did not find any P. nobilis individuals during the surveys. Although larval recruitment of this species has been recorded in larval collectors in the Columbretes Islands for several years after the mass mortality event (Kersting et al, 2020), we did not find any P. nobilis juveniles or recruits.…”
Section: Resultscontrasting
confidence: 80%
See 2 more Smart Citations
“…However, as expected, we did not find any P. nobilis individuals during the surveys. Although larval recruitment of this species has been recorded in larval collectors in the Columbretes Islands for several years after the mass mortality event (Kersting et al, 2020), we did not find any P. nobilis juveniles or recruits.…”
Section: Resultscontrasting
confidence: 80%
“…This indicated that the P. rudis juveniles might have been recruited around 2017-2018. It must be noted that 2017 was an outstanding year for P. nobilis larval recruitment (Kersting et al, 2020), with García-March et al (2020) reporting the same for P. rudis. Although no smaller juveniles were found in the surveyed circles, exploratory dives during the summer of 2021 showed that another successful recruitment event happened most probably in 2020, since many small juveniles (n > 10, 6-10 cm Carallot 2 (201 m 2 ) 0/0 0/0 0/0 4/2* in total length, i.e., about 1 year in age; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, healthy individuals of P. nobilis in the Mediterranean Sea have been confined at some localities: Thau Lagoon (France, Foulquié et al, 2020), Ebro's Delta andMar Menor Lagoon (Spain, Cabanellas-Reboredo et al, 2019;García-March et al, 2020), Venice Lagoon (Italy, Katsanevakis et al, 2021), Kalloni Gulf (Greece, Katsanevakis et al, 2021) and some localities in the Çanakkale Strait (Acarli et al, 2021). These areas not only act as refuges but are also potential larval exporting sites (Kerstling et al, 2020). Surveys to determine the disease mechanism of the pathogens and why some individuals are more resistant to pathogens should be carried out continuously.…”
Section: Discussionmentioning
confidence: 99%
“…The WMOP prediction system includes assimilation of satellite sea level and sea surface temperature measurements, as well as Argo temperature and salinity profiles and Ibiza Channel High-Frequency radar velocities, using the Ensemble Optimal Interpolation method described in Hernandez-Lasheras and Mourre (2018). The model was successfully used in a number of recent applications including the analysis of larval drift (Calò et al, 2018;Kersting et al, 2020), plastics or parasite dispersion (Cabanellas-Reboredo et al, 2019;Ruiz-Orejón et al, 2019;Compa et al, 2020), simulation of high-resolution observations (Fablet et al, 2018;Gómez-Navarro et al, 2018) or for dedicated products designed for instance for beach lifeguards or sustainable marine resources managers (Heslop et al, 2019 Three CMEMS models (GLO, MED, and IBI) cover the area that was most damaged by the Storm Gloria. This area of study is delimited by the Iberian Mediterranean coast and the Strait of Gibraltar to the west, the Gulf of Lions to the north, Corsica and Sardinia to the east and the North African coastline to the south.…”
Section: The Socib Regional Solution (Wmop)mentioning
confidence: 99%